Moist Heat Postconditioning to Increase Flap Survival - Engin, Murat Sinan; Demirtaş, Yener; Yağmur, Çaglayan; Öztürk, Nuray; Karacalar, Ahmet (Journal of Reconstructive Microsurgery, 2013)
One of the areas of interest within the discipline of reconstructive microsurgery is increasing the amount of tissue harvested along with a given pedicle and sustaining it. The aim of this study is to introduce moist heat postconditioning as a means to increase skin flap survival and evaluate its effectiveness. Eight white New Zealand rabbits weighing 2500 to 3000 g were separated into two groups. In both groups, the truncal flaps spanning four consecutive angiosomes were elevated bilaterally. Flaps were inset back afterwards, and to the flaps in the trial group moist heat was applied for 30 minutes. After 2 weeks, the flaps were photographed and flap survival ratios were calculated via ImageTool© software (University of Texas Health Science Center, San Antonio, Texas, USA). With an average necrosis ratio of 4.91% versus 37.31%, the flaps treated with moist heat displayed a significantly better survival rate (p = 0.000). This study presenting our new method demonstrates that application of moderate moist heat right after the flap inset provides a significant increase in flap survival and introduces a noninvasive, cost-effective, and safe method for clinical use.
Keywords: flap survival; moist heat; New Zealand rabbit